A USSD and android based tea farming information system: a case study of Mungania Tea Factory Company Limited - Njeru, Kenedy Munene (Strathmore University, 2017)
Current trends in information and communication technology have led to emergence of smartphones with faster wireless speeds, faster graphics, better screens, and faster chips, virtual and augmented reality. These phones are context-aware, have embedded physical sensors, have data exchange capabilities and allow installation of applications to perform almost any task. Tapping into this technology can lead to development of mobile information systems that promote sustainable farming through timely information access, especially in tea farming. The traditional practice in tea farming has seen dissemination of information through extension officers, Farmer Field Schools, mass media or farmer’s own experience. Consequently, this vital information is either accessed too late or when obsolete and sometimes completely lacking. Limited access to information has led to an information gap hence farmers practice poor planning and farming resulting to reduced revenue for both farmers and the Government of Kenya and environmental degradation. This study focused on developing a tea farming information system to meet the information needs of tea farmers. The nature of the study required the researcher to adopt deductive approach so as to compare the data findings against the existing literature through logical reasoning. A case study strategy was employed to gain a rich understanding of the research perspective with the focus being the tea farmers of Mungania Tea Factory Company Limited. Through qualitative and quantitative analysis the research findings can be generalised to all the tea farmers. Agile system development methodology was employed due to its sustainable development having testing integrated throughout the lifecycle. Scrum framework was adopted to allow for faster iteration with quick and accurate response to changes from user feedback. The contribution of this research concerns adoption of a tea farming information system to improve on productivity, service delivery and profitability, decision making and farmer protection from fraud and losses. Moreover, it facilitates the communication between the factory and the farmers giving easier access to extension services. It further enhances processing of more accurate and comprehensive information and generation of useful reports.
Thesis submitted in partial fulfillment of the requirements for the Degree of Master of Science in Mobile Telecommunication and Innovation at (MSc.MTI) at Strathmore University
Keywords: Information Access; Tea farming; Information System; USSD